Using Online Teaching Methods and Smart Learning Techniques to encourage Undergraduates to Study Sciences at Bethlehem University - Nader Abu Saad; Ahmad Atiyha (Journal of Arts, Literature, Humanities and Social Sciences, 2023)
The main goal of the current study is to explore how well online teaching and smart learning strategies worked to encourage students to pursue scientific courses at Bethlehem University. The study’s sample consisted of 55 male and female from the faculty of Science at Bethlehem University. The questionnaire was administered by the researchers using a quantitative research methodology. The findings reveal a statistically significant correlation between the degree of learning advantage from using software and technology and students’ ideas for changing the teaching and learning process. Nevertheless, there is not enough information to correlate performance before COVID-19 with students’ overall online learning experience. There is also no correlation between students’ expectations of the educational benefit of utilizing technology and software and their desired passion for learning the sciences.